Penerapan Manajemen Kualitas untuk Meningkatkan Kepuasan Pelanggan di Usaha Parfume Azzwars Jl. Raya Aru Lubuk Begalung, Kota Padang - Marila Sumiarti; Novela Rovitia; Ranti Yuli Yofani; Vicky Brama Kumbara (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Perfume is one of the human needs in the field of fragrances, where perfume has become part of the primary needs of some people. Therefore, it is very important to choose and use perfume with good quality products. Azzwars perfume is a perfume brand that is quite well known in West Sumatra. Azzwars perfume already has several branches in districts/cities in the West Sumatra region. Based on field surveys and observations made by the author at one of its branches on Jl. Raya Aru Lubuk Begalung looks empty of visitors. This is the author's interest to see how quality management is implemented to increase customer satisfaction in the business. The methods used in this research were observation and interviews. The results of this research on the implementation of quality management in Azzwars perfume are quite good, but it needs to be improved further in terms of marketing so that the Azzwars perfume business, especially the Lubuk Begalung branch, can be more widely known to the public. Thus, it is hoped that this research will be useful for business people and further research in increasing customer satisfaction in a business.